A invenção da criptomoeda: um olhar para os diferentes usos do bitcoin - Centeno, Andrey Fonseca (Universidade do Vale do Rio dos Sinos, 2018)
The information Era improved by the internet, enabled tools to promote one of the most relevant institutions of the world, the money. On the other hand, the role of the currency has less value due to electronic payment. As a result of this context, and the decades of development in the computer science and cryptography areas, the object this study was the cryptocurrency Bitcoin. This is the actual main digital currency because of open code characteristics, operates on a network called peer-to-peer, in which it is formed by thousands of users that intermediate the system, it supplies the market’s demands in a transparent way and enables technology that supports the system Bitcoin -Blockchain- to be present in other applications, etc. The perceptible growing use, more specifically the Bitcoin, justify the present study. This monography aims to comprehend how the Bitcoin, has been used by society, seeking to broaden the knowledge about this recent phenomenon. For this, an exploratory study was carried out, with a review of literature, current news that demonstrate the use of this cryptocurrency and about some cryptocurrency database. The intention here was to systematize information, in an organized way, that can collaborate to expand the understanding about the use of cryptocurrencies. With the study it was possible to understand that a Bitcoin coin can be considered a viable alternative to the current monetary system. The Blockchain technology enables a transparent system, without any history of fraud, and with significant utilities to different kinds of business. The range of uses of the Bitcoin, as this monography presents, indicates that the digital currency is a reality possible and should be treated as such by scholars. There is no course in any currency system in the capitalist world.
Keywords: Invenção; Moeda e Criptomoeda; Uso do Bitcoin; Sistema de Pagamento.Invention; Currency and Cryptocurrency; Use of Bitcoin; Payment System